A complex of putative acanthocolpid cercariae (Digenea) from Nassarius olivaceus and N. dorsatus (Gastropoda: Nassariidae) in Central Queensland, Australia - Barnett, Leonie J.; Smales, Lesley R.; Cribb, Thomas H. (Zootaxa, 2008)
Cercariae capricornia I–VI, six new cercariae putatively identified as belonging to the Acanthocolpidae, are described and named from prosobranch gastropods of the family Nassariidae collected from the intertidal zone in the Capricornia region, Central Queensland, Australia. Four species are reported from Nassarius olivaceus and two from N. dorsatus. The cercariae have a unique and complex three-dimensional body shape, including a keel, which differentiates them from previously described acanthocolpid cercariae. These are the first cercariae to be described from these gastropods.